1998
DOI: 10.1046/j.1464-410x.1998.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of urinary symptoms during adolescence

Abstract: Objective To determine the prevalence and natural hisreported by 4.7% of children at 11-12 years and 1.1% at 15-16 years. Some of the children reporting tory of urinary symptoms and incontinence among healthy adolescent schoolchildren.daywetting and nocturnal enuresis at 15-16 years old had not reported these symptoms at 11-12 years Subjects and methods A prospective longitudinal study using a confidential questionnaire administered to an old. Conclusion Urinary symptoms become less prevalent original cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 14 publications
6
47
0
4
Order By: Relevance
“…Up to 74% of enuretic adolescents had primary NE and 71% had monosymptomatic NE, which was unexpected; most patients could have been treated much earlier, before reaching adolescence. In females, symptomatic NE and UTI were significantly more frequent than in males, as already reported by Swithinbank et al [16]. About half of the girls with NE and UTI also complained of obstipation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Up to 74% of enuretic adolescents had primary NE and 71% had monosymptomatic NE, which was unexpected; most patients could have been treated much earlier, before reaching adolescence. In females, symptomatic NE and UTI were significantly more frequent than in males, as already reported by Swithinbank et al [16]. About half of the girls with NE and UTI also complained of obstipation.…”
Section: Discussionsupporting
confidence: 79%
“…In an attempt to assess the prevalence of NE in the general population, Cushing and Baller [15] investigated a group of 398 graduate and undergraduate students, finding a prevalence of NE of 3.8%. More recently, Swithinbank et al [16] in a longitudinal study on 1176 children, reported a prevalence of NE of 4.7% at 11-12 years old (3.5% and 6.2%, respectively, in females and males), decreasing to 1.1% at the age of 15-16 years (0.8% and 1.6%, respectively) In their series, NE was more frequent in males in both age groups, and day-wetting more frequent in females. Hellstrom et al [17] reported a prevalence of NE, respectively, of 0.7% in males and 0.6% in females at 17 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 clinical entities occur mainly in girls, [1][2][3] as manifestations of nonneuropathic bladder-sphincter dysfunction (NNBSD), and have always been associated with behavior problems; the International Classification of Diseases, 10th Revision, lists both "enuresis of nonorganic origin" and "urinary incontinence of nonorganic origin" in the category of mental and behavioral disorders. 4,5 For primary monosymptomatic nocturnal enuresis (MNE), this association has been studied quite extensively, [6][7][8][9][10][11][12] and in terms of temperament, emotional stress, and anxiety, most studies indicate that children with MNE are not different from those without.…”
mentioning
confidence: 99%
“…4,7,24,26 We have identified evidence supportive of a plausible pathophysiology in minimal TCS and preliminary information regarding the identification of patients subject to this pathophysiology (postulates one and two). Although only Class III evidence is available to support the efficacy of surgical filum division in minimal TCS, that Class III evidence is relatively abundant and uniformly positive.…”
Section: Neurosurg Focus / Volume 23 / August 2007mentioning
confidence: 93%